1990
DOI: 10.1063/1.103168
|View full text |Cite
|
Sign up to set email alerts
|

Real time i ns i t u observation of the film growth of hydrogenated amorphous silicon by infrared reflection absorption spectroscopy

Abstract: The growth of hydrogenated amorphous silicon films on Al substrates in a flow reactor was studied using infrared reflection absorption spectroscopy. All three hydride species (SiHx , x=1–3) in the growing films were detected as stretching and bending absorption bands in P polarization spectra. The dominant absorption band, initially originating from higher hydrides, was shifted to lower wave numbers with an increase of film thickness. A steep rise in absorption intensity at the initial stage and a time delay i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…This problem can be partially solved by studying the absorption during the initial stages of film growth for ultrathin a-Si:H films. [7][8][9][10][11] These experiments have indicated that mainly higher hydrides ͑SiH 2 and SiH 3 ͒ are present during the initial film growth, but one cannot distinguish whether these higher hydrides are present at the substrate-film interface and/or at the film-vacuum interface ͑the surface͒ for thicker films. In fact, these experiments do not reveal information about the surface composition and coverage under steady-state film growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This problem can be partially solved by studying the absorption during the initial stages of film growth for ultrathin a-Si:H films. [7][8][9][10][11] These experiments have indicated that mainly higher hydrides ͑SiH 2 and SiH 3 ͒ are present during the initial film growth, but one cannot distinguish whether these higher hydrides are present at the substrate-film interface and/or at the film-vacuum interface ͑the surface͒ for thicker films. In fact, these experiments do not reveal information about the surface composition and coverage under steady-state film growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…3. It is worth mentioning that surface Sill3, which was observed only weakly in the present case, is often observed strongly in such experiments as an Hg lamp (Wadayama, Suetaka, Sekiguchi, 1988) or metastable Ar-induced CVD of a-Si (Toyoshima, Arai, Matsuda & Tanaka, 1990) and hydrogen termination of Si(100) surfaces (Chabal, Higashi, Raghavachari & Burrows, 1989). The transition dipole moment of the Sill3 symmetric stretching vibration is parallel to the C3v symmetry axis, which is almost perpendicular to the substrate surface as already mentioned.…”
Section: Figurementioning
confidence: 48%
“…3 appears to consist mainly of surface Sill2 stretching (2113cm -1) and surface Sill stretching (2100 cm -1) vibrational modes. The vibration of the Sill contained in the bulk network, which was reported at 2000 cm -1 (Toyoshima, Arai, Matsuda & Tanaka, 1990;Lucovsky, Nemanich & Knights 1979), was not observed, as shown in Fig. 3.…”
Section: Figurementioning
confidence: 60%
“…As shown in Fig. 1, in-situ IR monitoring of surface H [3][4][5][6][7][8][9][10] on PECVD-grown a-Si:H films at 430…”
Section: Discussionmentioning
confidence: 99%
“…The almost fully hydrogen-terminated nature of a-Si:H growing surface is reported [3][4][5][6][7][8][9][10], so [H-Surf] can be assumed to be constant. As a result, it is concluded that the growth rate must show 1st order dependence on the SiH 3 density, as mentioned earlier.…”
Section: Reaction Modelsmentioning
confidence: 99%